INCOGNITO AND THE NEW DIPLOMACY: THE CASE OF TSAR PETER - M. Jansson (Vestnik MGIMO-Universiteta)
The aim of this article is to put Tsar Peter's traveling incognito in Holland and England into a wider context, to demonstrate that it was not an idiosyncratic choice on the Tsar's part but a mode of behavior taken from a new diplomatic protocol. One of the most vivid examples of the new mid-17th century conception of the term incognito is to be found in Peter's English experience. Using that experience as a focal point this article explains the evolution of the term itself in both literary usage and more broadly in diplomatic practice as it evolved at various congresses and assemblies of the period, beginning with the meetings preliminary to the signing of the Treaty of Westphalia. The article is based on various contemporary records and accounts, government documents and archives, as well as contemporary memoires. It concludes by showing that the practice of an ambassador or a monarch traveling incognito saved a governments' treasury the cost of elaborate ceremonials and a large entourage but more importantly for a monarch, it provided freedom of movement and escape from the constriction of the formalities of court rituals. Thus the actions of Peter I and also William III marked an important point in the transition from the formal ceremonial relations of personal monarchy at the beginning of the century to the later idea of the representation of the sovereign state by a regular corps of ambassadors and plenipotentiary ministers.